2010
DOI: 10.2215/cjn.07081009
|View full text |Cite
|
Sign up to set email alerts
|

The Circulating Inactive Form of Matrix Gla Protein Is a Surrogate Marker for Vascular Calcification in Chronic Kidney Disease

Abstract: Background and objectives: Vitamin K-dependent matrix Gla protein (MGP) acts as a calcification inhibitor in vitro and in vivo. The present study was performed to (1) determine plasma levels of the inactive, dephosphorylated, uncarboxylated MGP (dp-ucMGP) in a cohort of patients at different stages of chronic kidney disease (CKD) and (2) evaluate the association between dp-ucMGP levels on one hand and aortic calcification and mortality on the other.Design, setting, participants, & measurements: 107 patients (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
245
9
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(292 citation statements)
references
References 42 publications
(47 reference statements)
23
245
9
4
Order By: Relevance
“…The increased dp-ucMGP levels in uremia found in our study are consistent with a recent study showing increasing dp-ucMGP levels with higher chronic kidney disease (CKD) stages. 15 In this study, the levels seemed to be even higher than those of our previous study, 15 which may be because of the fact that we studied ESRD patients with long dialysis vintage and little to no residual renal function. Additionally, it could also point to a more pronounced vitamin K deficiency in our cohort of patients with long dialysis vintage.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The increased dp-ucMGP levels in uremia found in our study are consistent with a recent study showing increasing dp-ucMGP levels with higher chronic kidney disease (CKD) stages. 15 In this study, the levels seemed to be even higher than those of our previous study, 15 which may be because of the fact that we studied ESRD patients with long dialysis vintage and little to no residual renal function. Additionally, it could also point to a more pronounced vitamin K deficiency in our cohort of patients with long dialysis vintage.…”
Section: Discussioncontrasting
confidence: 58%
“…Correlation with PIVKA-II (this study) Increased levels in CKD patients 15 and dialysis patients (this study)…”
Section: Mgp Species Studies Interpretationmentioning
confidence: 67%
See 1 more Smart Citation
“…The biologically relevant concentrations of TS for this effect are unknown at the present time. A fourth mechanism may be related to STSinduced changes in serum inhibitors of vascular calcification (43,44), as described for the matrix-Gla-protein in previous studies with STS-treated rats (13). However, the concentrations required for this effect are unknown, too.…”
Section: Discussionmentioning
confidence: 92%
“…Five studies [10][11][12][13]24 reported on the association between mortality and dp-ucMGP in patients with aortic stenosis, 12 chronic 10 or end-stage kidney disease, 24 chronic heart failure, 11 or overt vascular disease. 13 The associations between all-cause mortality and dp-ucMGP were positive, 10-13 except in patients with advanced renal dysfunction, in whom this association was not significant.…”
Section: Discussionmentioning
confidence: 99%